An interactive application to analyse the existence of limit cycles using the describing function. Issue 17 (2022) - Lampón, Cristina; Diaz, Jose Manuel; Dormido, Sebastián; Costa-Castelló, Ramon
Abstract: This work describes the development of an interactive tool to illustrate the analysis of Lure systems through the use of the describing function. This is a classic tool that is usually introduced in the introductory courses of non-linear control systems present in the majority of master's degrees in control engineering.